Typologia przeszkód w realizacji prawa do sądu. Zastosowanie socjologicznej koncepcji praw człowieka Adama Podgóreckiego - Pilitowski, Bartosz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
The purpose of the paper is to propose a typology of obstacles to the implementation of the right to a fair trial, based on the sociological and legal concepts of Adam Podgórecki, Leon Petrażycki and Lawrence M. Friedman. The methods used by the author are a review of the literature on the implementation of the right to a fair trial in Poland, including the author’s own research and reports of public institutions. The result of the analysis is a typology with three main categories of obstacles: (1) those arising from the content of the regulations (direct, indirect and potential), (2) those related to the state of the justice system institutions (infrastructure and human resources), and (3) those arising from the legal culture (general and judicial). The author stresses that the most persistent barrier to the implementation of the right to a fair trial is the legal culture, especially the judicial culture. The author argues that a key element of the “full right to a fair trial”, as understood by Adam Podgórecki, is an internal sense of obligation on the part of justice system officials towards the subjects of that right, and not just towards the state or their superiors.